A Review of: College Disrupted: The Great Unbundling of Higher Education - Al-Hattab, Amira Ali (Journal of Educational and Psychological Sciences, 2019)
The writer believes that higher education is facing a big leap with the increasing size of the intranet in education, and the only way - in the writer’s opinion - to stay in the field of higher education is to keep up with this change by dismantling the traditional system of higher education. The book also discusses the apparent imbalance in the American higher education system - in the opinion of writer Ryan Craig - and what education should be compared to what it is now, comparing the book between the major universities that have endowments and those who do not have a standstill and compete in the field of higher education and seeks to be Similar to Harvard and elite universities. He believes that the American education system should establish a two-tier system: Harvard and its counterparts benefit from elite students, and a cheaper system harnesses the Internet and technology to benefit the rest of the students. So that they can get paid for what they pay instead of paying huge tuition fees going to support a university that does not benefit them and buildings that do not enhance their learning. In the opinion of the writer that the motivation to address this type of education is the widespread increase in the spread of the Internet and the huge costs required by education in its traditional form, which necessitates finding a solution to these problems and changes in the market of higher education.